ChemInform Abstract: AlNbBr8 — Preparation, Crystal Structure, and Vapor Pressure Studies. Issue 38 (September 2016) - Rogachev, Alexander V.; Zelenina, Ludmila N.; Chusova, Tamara P.; Virovets, Alexander V.; Sokolov, Maxim N.
Abstract: Red crystals of AlNbBr8 are prepared by degradation of Nb2 S4 Br4 in AlBr3 and [emim]Br under Ar (150 °C, 48 h) followed by dilution in benzene (4 °C, several d).